Kombinasi Pupuk Nanosilika dan NPK Terhadap Pertumbuhan Tanaman Jagung (Zea mays L var. pioneer 21) - Oktivani D.P. Hayati; Erma Prihastanti; Endah D. Hastuti (Jurusan Biologi FMIPA Universitas Cenderawasih, 2019)
Maize is one of food commodity in Indonesia. Maize pioneer 21 is a kind of high-yielding maize variety in Indonesia. One of the way able to be conducted to improve growth of maize plant is with fertilizing combination of nanosilica and NPK. This research aim to know the influence of fertilizing combination of nanosilica and NPK toward improving growth of maize plant and to know optimal concentration of combination nanosilica fertilizer and NPK in corn plants growth. Nanosilica is fertilizer that contains micronutrients Si while the NPK fertilizer contains macro nutrients NPK. Research conducted with Completely Ramdomized Design (CRD) with 6 combination factor: P0 (control), P1 (100% nanosilica), P2 (75% nanosilica + 25% NPK), P3 (50% nanosilica + 50% NPK), P4 (25% nanosilica + 75% NPK) and P5 (100% NPK) each has 3 replications. Parameter perceived by hat is high of plants, high of leaf, amount of leaf, wet heavy of maize plants and dry heavy of maize plant. Data to be analysed with Analysis of variance (ANOVA) level of signification 95%, continued by Duncan Multiple Range Test (DMRT) level of signification 95%. The results showed that the combination of nanosilica fertilization and NPK significantly affected the wet weight and dry weight of the Maize P-21. The optimal combination for the growth of Maize P-21 is the treatment of P4 (25% nanosilica+ 75% NPK). Key words: Zea mays L var. pioneer 21; combination; fertilizing; nanosilica; NPK